Problema Diagnostik dan Respons Kemoterapi pada Seorang Penderita Classical Limfoma Hodgkin Tipe Mixed Cellularity dengan Temporary Spontaneus Regression: [Difficult Case of Classical Hodgkin Lymphoma Mixed Cellularity Type with Temporary Spontaneous Regression] - Daniel Maranatha; Bintang Bestari (Jurnal Respirasi, 2017)
Background: Mixed cellularity classical hodgkin lymphoma (MCCHL) is the secound subtype of classical hodgkin lymphoma (cHL) which often happens. MCCHL is aggressive but has a relatively high recovery rate. The diagnosis of cHL is sometimes difficult. Spontaneous regression can occur in cHL but is very rare, temporary or permanent. CHL including diseases with a fairly high cure rate, about 80% of patients recover with first-line chemotherapy. Case: Male age 26 years, 9 months cough, shortness of breath, chest pain 8 months, 6 months fever disappear with enlargement of right supraclavicular lymph nodes appearing at 11 days before admission. Chest X-ray shows the presence of mediastinal mass supported by contrast thoracic CT scan. FNAB has been done three times with no meaningful results. In one of the chest radiographs and CT scan of the thoracic with contrast evaluation showed a reduction in tumor size. Open thoracotomy biopsy is performed with Hodgkin’s lymphoma results. On immunohistochemical examination obtained MCCHL. Chemotherapy with ABVD regimen was administered for three cycles with partial remission and was continued with 6 cycles with stable disease outcomes. Conclusion: Spontaneous temporary regression in cases with mediastinal tumor suspicion may occur in cHL and may cause difficulties in diagnosing. Open biopsy is required as a gold standard and has to be supported by immunohistochemical test. First-line chemotherapy response in cHL is good.